THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1946)
Abstract Two papers in the July 1946 issue of the journal The Accounting Review were originally presented before the May meeting of the American Association of Collegiate Schools of Business in the U.S. They were, The Public Accountant of Today and Tomorrow, by John W. Queenan, and Education for Public Accounting on the Collegiate Level, by Dean H.T. Scovill. In the discussion that followed the presentation of the papers, Professor W.A. Paton considered the topic treated by Dean Scovill and later made his remarks available for use in this article. The history of cost accounting has not yet been written. But when it is, its roots will be found reaching a long way back in time. And the wonder will be that, with such a start, it could take so long to evolve into the still uncoordinated cost accounting procedures that were typical of the nineteenth century. It is easier to recognize the factors which in the twentieth century produced an extraordinary acceleration in the development of accounting systems in general and cost accounting in particular, than it is to understand why a good start was so slow in gathering momentum.